Introduction to the Hospitality Industry / Seventh Edition - Barrows Clayton W.; Powers Tom (John Wiley & Sons, Ltd, 2009)
This book gives students the foundation they need to thrive in today's hospitality industry, covering everything from finance to operational issues. Perspectives on Careers in Hospitality, The Hospitality Industry and You, Forces Affecting Growth and Change in the Hospitality Industry, Food Service, The Restaurant Business, Restaurant Operations, Restaurant Industry Organization: Chain and Independent or Franchise, Competitive Forces in Food Service, On-Site Food Service, Issues Facing Food Service, Lodging, Lodging: Meeting Guest Needs, Hotel and Lodging Operations, Forces Shaping the Hotel Business, Competition in the Lodging Business, Travel and Tourism, Tourism: Front and Center, Destinations: Tourism Generators, Hospitality as a Service Industry, The Role of Service in the Hospitality Industry, Index.